Thinking about Secularism with Asad, Twenty Years after Formations - Khan, Sohaib (Religion and society, 2024)
Two decades after the publication of Talal Asad's Formations of the Secular (2003), secularism is in a global state of crisis. From the standpoint of secularism's liberal proponents, the rising tide of right-wing populisms from the United States and Brazil to Eastern Europe and India threatens liberal freedoms and democracy all over the world. In an age when liberal democracies struggle to uphold the rule of law and multiculturalism is losing its popular mandate to neofascist aspirations of nationhood, the vanguards of the liberal order have found renewed faith in the redemptive promise of secularism. Far from engaging in an honest reckoning of the consequences of neoliberal governance in perpetuating economic inequalities, class divides, racial resentment, and xenophobia, liberal elites are ever more convinced of the need to rehabilitate secularism as a bulwark against the scourge of authoritarian populism and religious obscurantism. It would seem that the last thing we need at this crucial historical juncture is a critique of secular formations of individual freedom, multicultural assimilation, democratic representation, just war, and human rights, among others. To those who find it imperative to salvage secularism, such critiques are not only untimely but also play into the hands of nefarious interests bent on sabotaging liberal democracy. Recourse to fearmongering becomes an effective tactic of shutting down critiques of secularism: if you are so suspicious and disparaging of the liberal freedoms you enjoy under the secular state, would you rather live in a theocracy or tolerate another right-wing demagogue in the White House?